Uveal tract changes associated with Canine Monocytic Ehrlichiosis (CME) (Research, Society and Development, 2021)
Canine Monocytic Erlichiosis (CME) is a disease caused by the bacterium Ehrlichia canis, transmitted through the bite of the tick Rhipicephalus sanguineus during blood meal. Infection with this bacterium is highly prevalent nationwide, causing high morbidity and mortality rates in domestic dogs. Ophthalmic changes are considered of great importance, as they can cause permanent blindness and may still be the only clinical manifestation of the disease. The objective of this paper is to approach the main ophthalmic changes associated with CME, as well as its pathophysiology, diagnostic methods, therapeutic options and prognosis, aiming a better understanding of these signs within the small animal internal medicine. A bibliographic review was carried out looking for correlation studies between CME and ophthalmic changes in dogs, where was observed that the uvea is the most affected structure because its tissue is highly vascularized and immunosensitive. The ophthalmic consequences in these animals can be serious and permanent when the diagnosis and treatment are late, therefore knowledge in this area is of great value to veterinarians that work with the general practice of small animals.